1995
DOI: 10.1046/j.1471-4159.1995.64010354.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Stages in Neurite Formation Distinguished by Differences in Tubulin Metabolism

Abstract: Changes in tubulin solubility during neurite formation were studied biochemically using rat dorsal root ganglion neurons in culture. When fractionated with Ca" -containing buffer at low temperature, a considerable proportion of total cellular tubulin was recovered in the insoluble fraction . We designated this cold/Ca 2+insoluble tubulin (InsT) and distinguished it from cold/ Ca" -soluble tubulin (SoIT) . From the relative amount of InsT, neurite formation was found to proceed through two distinct stages . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Axons of DRG elongated rapidly within the first 3 days of culture under these conditions, attaining a length of 240 Ϯ 10 m, and continued to elongate at a slower rate (i.e., to 250 Ϯ 10 m) by day 7 in cultures. As shown previously [e.g., Dahl, 1988;Sekimoto et al, 1995], this period (days 3-7) is accompanied by a transition of the axonal cytoskeleton from a form consistent with rapid elongation to one that imparts stability to axons, accomplished in part by the accumulation of phospho-NFs (Fig. 1).…”
Section: Resultssupporting
confidence: 74%
“…Axons of DRG elongated rapidly within the first 3 days of culture under these conditions, attaining a length of 240 Ϯ 10 m, and continued to elongate at a slower rate (i.e., to 250 Ϯ 10 m) by day 7 in cultures. As shown previously [e.g., Dahl, 1988;Sekimoto et al, 1995], this period (days 3-7) is accompanied by a transition of the axonal cytoskeleton from a form consistent with rapid elongation to one that imparts stability to axons, accomplished in part by the accumulation of phospho-NFs (Fig. 1).…”
Section: Resultssupporting
confidence: 74%
“…The time frame of these changes in expression (high upon initial plating, and reaching a lower steady-state level after 12 days in culture) also correlates closely with a study of process maturation, which identified two stages of neurite growth on the basis of microtubule metabolism. The first stage, of active growth, occurred within the first week of plating in cultured dorsal root ganglion neurons, and the second stage, of maturation, occurred during the second week in culture (Sekimoto et al, 1995). Our data provide more evidence to support the role of ARMS/ Kidins220 in process outgrowth.…”
Section: Discussionmentioning
confidence: 50%